MARITIME CONNECTIVITY TERKAIT ASEAN TRADE IN GOODS AGREEMENT - Geraldi, Aldo Rico (Justitia et Pax, 2018)
This research aims to analyze free trade within the framework of the ASEAN Free Trade Agreement and the ASEAN Trade in Goods Agreement as well as the ASEAN Maritime Connectivity and ASEAN Trade in Goods Agreement in the framework of free trade. This research uses normative legal research methods. The results of this research indicate that AFTA is a major driver in the ASEAN free trade sector through the CEPT mechanism. ATIGA was then born focusing on reducing and abolishing ASEAN trade tariffs. As for ASEAN connectivity is the relationship between countries that facilitate the flow of capital, goods, services, and people within the region to become a barrier-free trade route for trade liberalization by sea.Keywords: ASEAN Free Trade Agreement, ASEAN Trade in Goods Agreement, ASEAN Maritime ConnectivityABSTRAKPenelitian ini bertujuan untuk menganalisis perdagangan bebas dalam kerangka ASEAN Free Trade Agreement dan ASEAN Trade in Goods Agreement serta keterkaitan ASEAN Maritime Connectivity dan ASEAN Trade in Goods Agreement dalam kerangka perdagangan bebas. Penelitian ini menggunakan metode penelitian hukum normatif. Hasil penelitian ini menunjukkan bahwa AFTA menjadi penggerak utama dalam sektor perdagangan bebas ASEAN melalui mekanisme CEPT. Kemudian lahirlah ATIGA yang berfokus pada tindakan pengurangan dan penghapusan tarif perdagangan ASEAN. Sedangkan terkait dengan konektivitas ASEAN merupakan keterhubungan negara-negara yang memudahkan aliran modal, barang, jasa, dan orang dalam kawasan agar menjadi jalur perdagangan bebas hambatan untuk liberalisasi perdagangan melalui laut.Kata Kunci: ASEAN Free Trade Agreement, ASEAN Trade in Goods Agreement, ASEAN Maritime Connectivity